HUBUNGAN PERAN GURU DENGAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS XI-1 DI SMA ISLAM 1 SURAKARTA TAHUN PELAJARAN 2024/2025 - Muhammad Rihardin; Mukhlis Fathurrohman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the relationship between teacher roles and the quality of Islamic Religious Education (PAI) learning among class XI-1 students at SMA Islam 1 Surakarta in the 2024/2025 academic year. The background of this research lies in the crucial importance of teacher roles in improving education quality, especially in PAI learning which aims to shape students’ character and morals. The research employed a quantitative correlational design with a sample of 52 students. Data were collected using closed-ended Likert scale questionnaires to assess students’ perceptions of teacher roles and PAI learning quality. The instruments were validated and found reliable prior to analysis. Data analysis included assumption tests (normality and linearity) and Pearson Product Moment correlation testing. The results showed that the teacher’s role in PAI was in the good category (mean score 67.88), and similarly the PAI learning quality was good (mean score 77.13). There was a significant positive correlation between teacher roles and PAI learning quality (r = 0.445, p = 0.001). This indicates that the more optimal the teacher’s role as an educator, mentor, facilitator, motivator, and evaluator, the better the quality of PAI learning. These findings underscore the importance of teacher roles in enhancing PAI learning quality.